Iteration Methods for Linear Systems with Positive Definite Matrix - Longquan Yong; Shouheng Tuo; Jiarong Shi (Universitas Ahmad Dahlan, 2016)
Two classical first order iteration methods, Richardson iteration and HSS iteration for linear systems with positive definite matrix, are demonstrated. Theoretical analyses and computational results show that the HSS iteration has the advantages of fast convergence speed, high computation efficiency, and without requirement of symmetry.